Iowa Birdline update, December 26, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for December 26, 1994. Highlights of the update include sightings of a Say's Phoebe, Long-tailed Ducks, a White-winged Scoter, a Surf Scoter, a Lesser Black-backed Gull, and a Mew Gull. Also included are handwritten notes for the next week's update with sightings of Short-eared Owls, several species of Gulls, and a Sandhill Crane. Epson - sheet feed/flatbed